Preparation and graft-copolymerization of hydrogenated natural rubber in latex stage - Ha, Nguyen Thu; Kaneda, Keisuke; Naitoh, Yoshitaka; Fukuhara, Lina; Kosugi, Kenichiro; Kawahara, Seiichi (Journal of applied polymer science, 2015)
ABSTRACT Preparation and graft‐copolymerization of hydrogenated natural rubber are performed in latex stage after removal of proteins from the rubber with urea and surfactant. Hydrogenation of deproteinized natural rubber (DPNR) latex is carried out with palladium catalyst under hydrogen atmosphere. The hydrogenated DPNR (HDPNR) is crosslinked with a peroxide followed by graft‐copolymerization of styrene (Sty) and acrylonitrile (AN) in latex stage in order to prepare a graft‐copolymer of crosslinked HDPNR with poly(Sty‐co‐AN) (HDPNR‐graft‐PSAN). Characterization of the products is performed by nuclear magnetic resonance spectroscopy. The conversion of hydrogenation is investigated with respect to the catalyst feed, acidity (pH), and dry rubber content. In the resulting HDPNR‐graft‐PSAN, mole fraction of AN and Sty is 1.4 and 5.8 mol %, respectively. The graft‐copolymer is used to improve properties of PSAN as an impact modifier. The Charpy impact strength of crosslinked HDPNR‐graft‐PSAN/PSAN is about eight times as high as that of PSAN. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42435.